Calcium Oscillations and its Functional Siognificance in Chronobiology of Pancreatic Î²-Cells: The Art of Discovering Science (Ibrahim Medical College Journal, 2009)
doi: 10.3329/imcj.v1i1.2891  Ibrahim Med. Coll. J. 2007; 1(1): 21-31